The ESG-Innovation Disconnect: Evidence from Green Patenting - Cohen, Lauren H.; Gurun, Umit G.; Nguyen, Quoc H. (Management Science, 2026)
We document that traditional energy firms are key innovators in the United States’ green patent landscape. These firms produce more, and significantly higher-quality, green innovation. In many green technology spaces, they appear to be influential first movers and to produce ongoing foundational aspects of innovation and commercialization on which other alternative energy producers build. They additionally invest significantly in labor and capital to complement these green innovations. These traditional energy firms, however, receive significantly lower environmental, social, and governance (ESG) scores and fund flows and are not rewarded for incremental green innovation. This behavior is consistent with a competitive response by traditional energy firms to preempt obsolescence of current technology by investing in future replacement technologies. This paper was accepted by Bo Becker, finance. Funding: Funding was provided by the National Science Foundation [Grant SciSIP 1535813] and the Fordham University Gabelli School of Business—PVH Corp. Global Thought Leadership Grant on Corporate Social Responsibility. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2024.09124 .